Sikap Siswa Kelas X Ips Pada Mata Pelajaran BiologiProgram Peminatan Di SMA Negeri Colomadu SemesterGenap Tahun Ajaran 2015/2016 - Wahidaturrahmah, Nur Lailia, Dr. Sofyan Anif, M.Si, Drs. Djumadi, M.Kes (2016)
Proclivity program is the process of choise and decision for student in learning group, across course and courses. Curiculum 2013 implementation applyed across Biology course for social student in grade X. This study aimed to describe the attitude of social student learning Biology course. The method of this research is direct bservation to class and interview with Biology's teacher.Type of this research is qualitative descriptive with research strategy is study case. Research result show that the average representation attitude score is 65,38% (sufficient).The aspect of discipline in initial learning is 62,50% (sufficient), tools of learning is 62,50%(sufficient), anthusiastic is 77,78% (good), experient of learning is 65,83% (sufficient),and measure in the last is 65,38% (sufficient).